Prevention and Management of Type II Diabetes Chronic Complications: The Role of Polyphenols (Mini-Review) - Pani, Arianna; Baratta, Francesco; Pastori, Daniele; Coronati, Mattia; Scaglione, Francesco; del Ben, Maria (Current Medicinal Chemistry, 2022)
The numerous complications of diabetes may be at least in part generated by the oxidative stress associated with the constant state of hyperglycemia. Polyphenols are plant-based secondary metabolites that have high potentials in the prevention and treatment of some diseases, in particular those that involve oxidative stress, such as complications of diabetes. The purpose of this narrative review is to show the main evidence regarding the role of polyphenols in treating and preventing these complications. For the bibliographic research, the papers published up to March 15, 2021, were considered, and the search terms included words relating to polyphenols, their classes and some more known compounds in association with the complications of diabetes. There are numerous studies showing how polyphenols are active against endothelial damage induced by diabetes, oxidative stress and hyperinflammatory states that are at the origin of the complications of diabetes. Compounds such as flavonoids, but also anthocyanins, stilbenes or lignans slow the progression of kidney damage, prevent ischemic events and diabetic nephropathy. Many of these studies are preclinical, in cellular or animal models. The role of polyphenols in the prevention and treatment of diabetes complications is undoubtedly promising. However, more clinical trials need to be implemented to understand the real effectiveness of these compounds.
Keywords: stilbenes